An examination of teaching practice experiences for undergraduate students: A case study from the department of mathematics and science education at the university of Botswana - Thabologo, Fine; Mogotsi, Salome Maemo; Kesianye, Sesutho Koketso (Asian Journal of Contemporary Education, 2025)
This study aimed to document the experiences of undergraduate student teachers specializing in Mathematics and Science Education during their Teaching Practice in Botswana. The sample consisted of third- and fourth-year students from the Mathematics and Science Education department at the University of Botswana who had participated in Teaching Practice. A concurrent embedded design was utilized, and data was gathered from 150 student teachers using questionnaires and interviews. The results indicated that student teachers perceived teaching practice as an essential experience for developing teaching skills. The findings also suggested that the placement system was adequate. Nonetheless, the study identified several challenges including poor communication between the Teaching Practice Office and schools, lecturers hastily conducting the supervisory process, insufficient resources in schools, and limited support from mentor teachers. Additionally, the study found that the duration of the teaching practice was insufficient. As a result, it was recommended that the university strengthen its partnership with host schools by organizing awareness seminars, formulating and implementing relevant policies, and facilitating effective two-way communication to foster a supportive environment. The study also recommended that the university develops and executes policies and programmes to provide sufficient time for Teaching Practice to improve its effectiveness.